An X-Y cutting table for a hand held plasma torch - Lim, Frederick (Animo Repository, 2001)
The study presents an X-Y cutting table specially designed for a hand held plasma torch (Powermax 350). The machine can cut any metal. Machine's cutting path moves along the X, Y and Z- axes. Stepper motor actuator where used to drive the mechanical part of the machine, which is interfaced with the Personal Computer. The software allows simulation during execution. Drawings where extracted from Autocad using DXF files.